1976
DOI: 10.1002/cber.19761090832
|View full text |Cite
|
Sign up to set email alerts
|

Notiz über die Reaktion der (Pentahalogenäthylimido)phosphorsäure‐trichloride mit Ammoniumchlorid zu sechsgliedrigen C,N,P‐Ringsystemen

Abstract: Kukhar und Mitarbb. I) berichten, durch Umsetzung von (Pentachlorathy1imido)phosphorsauretrichlorid mit NH,CI das 4-gliedrige Ringsystem 2,2-Di~hlor-4-trichlormethyl-l,3,2~~-diazaphosphet gemal3 (1) erhalten zu haben.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1977
1977
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…Ausgangsverbindungen für die hier beschriebenen Synthesen sind das 2,2-Difluor-4,6-bis(trifluormethyO-l^^^A^-triazaphosphinin (1) [1] bzw. das 2,2-Dichlor-4,6-bis(trifluormethyl)-l,3,5,2A 5 -triazaphosphinin (2) [1].…”
Section: Ergebnisse Und Diskussionunclassified
“…Ausgangsverbindungen für die hier beschriebenen Synthesen sind das 2,2-Difluor-4,6-bis(trifluormethyO-l^^^A^-triazaphosphinin (1) [1] bzw. das 2,2-Dichlor-4,6-bis(trifluormethyl)-l,3,5,2A 5 -triazaphosphinin (2) [1].…”
Section: Ergebnisse Und Diskussionunclassified
“…The synthesis of the title compound, namely the 1,3,2λ 5 -diazaphosphete F has been claimed in 1973; however, soon after Glemser demonstrated that it was in fact a mixture of 6-membered rings G and H . Although the mechanism of the reaction has not been elucidated, it seemed quite possible that the observed products G and H resulted from a disproportionation of the 4-π-electron 4-membered ring F , arguing again for the high instability of the 4-π-electron 4-membered heterocycles.…”
Section: Introductionmentioning
confidence: 99%